Classification of anemias - Akarsu, Saadet (Turkish Pediatrics Assoc, 2009)
The purpose of this chapter is to provide both a more general classsification of the anemias and an initial diagnostic approach to the patient with this laboratory finding. Anemia is defined as a reduction in red cell mass (RBC) or in blood hemoglobin concentration (Hb), or in hematocrit (Hct) per cubic millimeter. Anemias may be classified on a physiologial or a morphological basis. The initial diagnostic approach to the anemic patient includes a detailed history and physical examination and a minimum of essential laboratory tests. The blood smear is very helpful in the diagnosis of anemia. If the clinician considers these options in an inclusive but systematic fashion, direct screening tests can be ordered and expert consultation avoided. (Turk Arch Ped 2009; 44 Suppl: 6-13)
Anemilerin siniflandirilmasi
Keywords: Anemic child; classification; diagnosis